Maize nodal root growth maintenance during water deficit: metabolic acclimation and the role of increased solute deposition in osmotic adjustment - McCubbin, Tyler J.; Greeley, Laura A.; Mertz, Rachel A.; Sen, Sidharth; Griffith, Amelia E.; King-Miller, Shannon K.; Riggs, Kara; Niehues, Nicole D.; Pareek, Akanksha; Bryan, Victoria J.; Zeng, Shuai; Becker, Cheyenne; et al. (Frontiers in Plant Science, 2025)
Maize (Zea mays L.) nodal roots are characterized by their ability to maintain elongation under water deficit conditions that inhibit the growth of other organs. Physiological and molecular mechanisms underlying this response were investigated using a divided-container root growth system to impose uniform and steady water deficit (WD) conditions around the nodal roots of maize cv. FR697. Kinematic growth analysis demonstrated that continued nodal root elongation under water deficit involves maintenance of both growth zone length and rates of cell production from the meristem. Nodal roots that maintain growth during WD exhibit increased rates of net solute deposition throughout the growth zone that enable osmotic adjustment and continued tissue expansion. These abilities differ from the maize primary root, which exhibits impairment of both cell expansion and cell production when grown under similar water deficit conditions. Integration of transcriptomic and metabolomic profiling revealed molecular signatures of nodal root growth maintenance, including central transcriptional responses and metabolic pathways related to osmolyte accumulation, hormone signaling, and ROS homeostasis. Several metabolic responses differed from previous characterization of the primary root, including taurine accumulation and proline synthesis via the saccharopine pathway. Further, our analysis showed that metabolic acclimation rather than transcriptional control dominated the water deficit response of the nodal root growth zone. The study highlights novel insights into the interplay of morphogenic and metabolic responses that regulate the remarkable ability of nodal roots to maintain elongation under water deficit conditions.